2019
DOI: 10.3390/app9245389
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids Overproduction in Dunaliella Sp.: Transcriptional Changes and New Insights through Lycopene β Cyclase Regulation

Abstract: Dunaliella is a green microalga known for its ability to produce high levels of carotenoids under well-defined growing conditions. Molecular responses to the simultaneous effect of increasing salinity, light intensity and decrease of nitrogen availability were investigated in terms of their effect on different metabolic pathways (isoprenoids synthesis, glycolysis, carbohydrate use, etc.) by following the transcriptional regulation of enolase (ENO), 1-deoxy-D-xylulose 5-phosphate synthase (DXS), lycopene β-cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…Previous studies reported that lycopene cyclase uses FAD as a cofactor. 48 Moise et al 49 reported that most of the enzymes involved in the transformation of lycopene and carotene are membrane-bound. Similarly, in NoLCYB the binding site is close to the membrane helix and the FAD-binding domain is present near the enzyme (data not shown).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Previous studies reported that lycopene cyclase uses FAD as a cofactor. 48 Moise et al 49 reported that most of the enzymes involved in the transformation of lycopene and carotene are membrane-bound. Similarly, in NoLCYB the binding site is close to the membrane helix and the FAD-binding domain is present near the enzyme (data not shown).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Nevertheless, bioactive compounds also can be synthesized from secondary metabolism with cosmetics and phar-maceutical aims [24,52]. Similarly, Cyanobacteria from marine and freshwater sources are known to produce a variety of bioactive compounds (secondary metabolites) that are derived from mixed biosynthetic pathways endowed with diverse biological activities, including antiviral, antibacterial, antifungal, antimalarial, antitumoral, and antiinflammatory properties [53][54][55].…”
Section: Compositions and Technologies For Photoautotrophic Productio...mentioning
confidence: 99%
“…Dunaliella sp. carotenoids are mainly triggered by two essential genes CGP and LCYB [ 171 ]. In Rhodotorula mucilaginosa , CAR gene cluster synthesizes carotenoids [ 172 ].…”
Section: Pigment Gene Cassettesmentioning
confidence: 99%